Online Course as a Part of Online Learning: A Review of Its Learning-Teaching Methods, Perspectives, and Potentialities - Hokianto, Hugo Fostin (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
The need for a resilience business is rising as the world has entered the post-pandemic era. Every change made during the pandemic restriction has been reverted, and some changes are irreversible, as they already become a part of people's lives. Although the pandemic is over, education has to continue to teach people, and there is a demand for people who want to learn new skills or soft skills for work or to be productive. Online course offers a solution for people in learning, as it is a part of e-learning and online learning. Many people have taken the initiative to be involved in the online course, making revenues. This paper’s purpose is to give insights about online courses as a part of online learning, and the effect it can have in education from methods, perspectives, and potentials it has. Hence, this paper explains three main points: 1) Explaining the learning method in online courses, 2) Understanding the differences between E-Learning and traditional teaching, and 3) the Potential of Online Courses. This paper uses a qualitative descriptive research design, using a literature review to collect data. The results of this paper gave a more refined definition of E-Learning and Online Courses and described the differences in learning methods, with asynchronous learning consisting of Massive Open Online Courses and YouTube and synchronous learning consisting of webinars and subscription-type online courses; students interested in E-Learning according to survey with instructors pointing out advantages and disadvantages, and potentials in selling MOOCs in Udemy, Youtube, paid webinars, and subscription-type online course paid monthly or annually.